A new species of Thraulodes Ulmer (Ephemeroptera: Leptophlebiidae), with additional data on the anatomy of the reproductive tract - Cortes,Isabel Cristina Hernández (2021)
ABSTRACT A new species of Thraulodes Ulmer 1920 is described based on nymphs and imagos from Tapias river, Caldas department, Colombia. The mature nymphs were reared until the emergence of the imagos. Thraulodes latinus sp. n. can be distinguished from other species of the genus by: In males, the forewing without cross veins basal to bullae and with 11-14 cross veins distal to bullae, abdominal and legs color pattern, styliger plate redounded, with a long and digitiform median projection and shape of penes with apicolateral area forming an “ear-like” projection. In nymphs, the claws with eight denticles and the general coloration pattern. Additionally, data on the anatomy of the reproductive tract of both the male and female imago of the new species are presented.